Epidemiological profile of viruses holders who conduct HIV treatment in service specialist care in Sinop-MT - Trentin, G.C. Carmen; Oliveira, R.R. Rocha; Cunha, A.N. Nogueira (Scientific Electronic Archives, 2016)
Abstract.The AIDS epidemic is going through a constant dynamic and is difficult to assess the vulnerability group. This study aims to raise the social and epidemiological profile of HIV patients undergoing treatment and / or monitoring in Specialized Care Service (NCS) Sinop - MT. This is an exploratory research with quantitative analytical approach, performed with 36 subjects in the period from February to August of 2013.O result was 75% are female, 22% aged 45-49 years, 39% color white, 56% married / stable, 88% heterosexual, 56% have primary education, 69% with incomes between two and three times the minimum wage, and 56% what bothers disease is prejudice, 97% contracted the virus sexually , 72% of individuals using HAART, 47% had CD4 counts above 500 células/mm3. Infelizmente prejudice is still the biggest hurdle in fighting HIV / AIDS. Â